ANALISIS NILAI-NILAI KEMANUSIAAN DALAM NOVEL “DEBU YERUSSALEM” KARYA QUODVULTDEUS BAGASKORO - Moh Syamsul Ma’arif; Hafifah Hafifah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
The value of humanity is an attitude or behavior among fellow human beings that is related to mutual tolerance, freedom, openness, fairness, fairness, honesty, between religious communities. Novel Dust Dust Jerusalem tells the story of a difference that occurred between Roman religious, Christian, and Jewish. This difference resulted in a disaster for humans at that time. The method used in this research is Qualitative Descriptive. The approach used is the Sociology of Literature approach. The research data source is the novel DebuYerussalem by QuodvultdeusBagaskoro. The research instrument uses tables of lattice instruments of human values and corpus data. Data collection techniques using text analysis techniques. The validity used is a flowing technique that includes three components of activity namely data reduction, data presentation, and conclusion drawing. The stages of research carried out consist of several stages, namely the initial stage, the implementation phase, and the completion phase.Based on the results of the study, it can be concluded that in the novel DebuYerussalem by QuodvultdeusBagaskoro contains human values that are very useful for the readers. Humanity values contained in the novel cover three aspects of aspects, namely the aspect of justice, fair in deciding a case based on the law and religion that has been determined. Not taking sides with one party but prioritizing peace, choosing for the common good for peace between people. Aspects of suffering, physical and mental suffering with acts of torture include hitting, kicking, killing carried out on humans. Feeling a sense of hurt in humans.The aspect of love, the realization of compassion, compassion, attention expressed by responsible behavior.Providing a sense of devotion and comfort for others.Keywords: Values, humanity, Dust of Jerusalem